1992
DOI: 10.1017/s0890037x00035752
|View full text |Cite
|
Sign up to set email alerts
|

Banded Herbicide Applications and Cultivation in a Modified No-till Corn (Zea mays) System

Abstract: The acceptance of no-till crop production systems has been limited due to expected problems with weed management. Field experiments were established at two locations in Ontario in 1988 and one location in 1989. Band or broadcast applications of preemergence (PRE) combinations of high or low label rates of atrazine with or without metolachlor or inter-row cultivation, were evaluated for their effectiveness in controlling annual weeds in no-till corn. At each location, different herbicide and cultivation combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
4

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 13 publications
3
20
0
4
Order By: Relevance
“…Em trabalhos com a cultura do milho, Eadie et al (1992) obtiveram redução do rendimento de grãos de 28 a 48%, variável em função do local de avaliação, com a aplicação de herbicidas na linha da cultura, em comparação com a aplicação em área total. Neste caso, a complementação da aplicação de herbicidas na linha com uma capina na entrelinha da cultura apresentou o mesmo rendimento de grãos, em comparação com o controle em área total.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Em trabalhos com a cultura do milho, Eadie et al (1992) obtiveram redução do rendimento de grãos de 28 a 48%, variável em função do local de avaliação, com a aplicação de herbicidas na linha da cultura, em comparação com a aplicação em área total. Neste caso, a complementação da aplicação de herbicidas na linha com uma capina na entrelinha da cultura apresentou o mesmo rendimento de grãos, em comparação com o controle em área total.…”
Section: Resultsunclassified
“…A impossibilidade de revolvimento do solo na semeadura direta implica a não-eliminação das plantas daninhas por meio da operação de preparo do solo para a semeadura (Eadie et al, 1992) e, também, dificulta a utilização da capina como medida de controle das ervas após o estabelecimento da cultura. Por outro lado, a manutenção da cobertura vegetal sobre o solo no sistema de semeadura direta restringe a emergência de plantas daninhas, em comparação com o solo descoberto (Theisen et al, 2000).…”
unclassified
See 1 more Smart Citation
“…Nevertheless, the amount of herbicide was reduced by 67% compared with the broadcast application at the full rate. In other studies, successful weed control was achieved with band-applied herbicides followed by inter-row cultivation with no-till corn (Eadie et al 1992), chisel plow and no-till soybeans (Hooker et al 1997), conventionally tilled soybeans (Buhler et al 1992;Hooker et al 1997) and conventionally tilled white beans (Woolley 1989).…”
Section: Results and Discussion Weed Controlmentioning
confidence: 99%
“…Buhler et al (1992) reported that two inter-row cultivations in conventional-tilled soybeans substituted for 50-75% of the control provided by herbicides. Eadie et al (1992) reported excellent weed control in no-till-planted corn with a residual herbicide bandapplied followed by inter-row cultivation.…”
Section: Mots Clés: Travail De Conservation Maîtrise Des Mauvaises Hmentioning
confidence: 99%